2022
DOI: 10.1080/02813432.2022.2036480
|View full text |Cite
|
Sign up to set email alerts
|

GP strategies to avoid imaging overuse. A qualitative study in Norwegian general practice

Abstract: Objectives The aim of the study was to identify general practitioners’ (GPs) strategies to avoid unnecessary diagnostic imaging when encountering patients with such expectations and to explore how patients experience these strategies. Design, setting and subjects We conducted a qualitative study that combined observations of consultations and interviews with GPs and patients. A total of 24 patients visiting nine different GPs in two Norwegian urban areas were included i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
12
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 23 publications
3
12
0
Order By: Relevance
“…Kool and colleagues found that 67% of their responding GPs acknowledged that low-value care practice was regularly provided in general practice [ 31 ]. There may be many reasons for high referral rates, such as time pressure and patient-related factors [ 31 , 32 ], (un)familiarity with guidelines [ 33 ], and difficulties in handling professional uncertainties [ 10 ]. Several strategies are used to avoid imaging overuse [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Kool and colleagues found that 67% of their responding GPs acknowledged that low-value care practice was regularly provided in general practice [ 31 ]. There may be many reasons for high referral rates, such as time pressure and patient-related factors [ 31 , 32 ], (un)familiarity with guidelines [ 33 ], and difficulties in handling professional uncertainties [ 10 ]. Several strategies are used to avoid imaging overuse [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…There may be many reasons for high referral rates, such as time pressure and patient-related factors [ 31 , 32 ], (un)familiarity with guidelines [ 33 ], and difficulties in handling professional uncertainties [ 10 ]. Several strategies are used to avoid imaging overuse [ 32 ]. Interventions targeting referrers, including decision support tools, such as the ESR iGuide, guideline implementation, education, feedback to referrers, using various hand-outs, either alone or in combination, have been tried out.…”
Section: Discussionmentioning
confidence: 99%
“…Participants provided demographic information such as their length of time in practice, and their experiences of patients requesting radiological referrals. The interview was then guided by open-ended questions developed through an extensive literature search 10,13,[21][22][23][24] and expert consultation with the imaging department's healthcare professionals, for example, radiologists, specialists and physiotherapists. These included the types of exams frequently requested, the characteristics of patients, their concerns and demographics of patients likely to request referrals.…”
Section: Recruitmentmentioning
confidence: 99%
“…Overall, the evolving landscape of patient consumerism, driven by increased internet access and patient‐centred expectations, necessitates a response from GPs. The perceived pressure on GPs to order diagnostic tests has been explored by Griffith et al 19 with additional studies centred on patient–GP communication, concerns over unnecessary expenditure in imaging 20 and avoiding imaging overuse 21 . However, there is limited research on how GPs personally respond to patients requesting radiological studies.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation